2014
DOI: 10.4236/ajor.2014.45030
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Coping Strategies Adopted by Postgraduate Students of Agricultural Education in Thesis Writing in Nigerian Universities

Abstract: The study investigated challenges encountered and coping strategies adopted by postgraduate students of agricultural education in writing thesis in Nigerian universities. Two research questions and two hypotheses guided the study. The study was conducted in Nigerian universities offering post-graduate programme in agricultural education. The population for the study was 118 made up of 14 postgraduate diploma, 66 masters and 38 doctoral students writing thesis in agricultural education. The entire population wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
2
10
1
Order By: Relevance
“…From the table it can be seen that the majority of the respondents agreed that they encountered one or more of the following challenges: lack of adequate funding, inability to source relevant materials for their research topic, inability to understand and cope with the relationship between concepts as applied to the topic approved for them by their various supervisors, and inability to cope with other academic assignments assigned by supervisors in addition to their course work/project. These findings are consistent with those of Olaitan et al (2009), Tichaona -Onias (2012, and Asogwa et al (2014).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…From the table it can be seen that the majority of the respondents agreed that they encountered one or more of the following challenges: lack of adequate funding, inability to source relevant materials for their research topic, inability to understand and cope with the relationship between concepts as applied to the topic approved for them by their various supervisors, and inability to cope with other academic assignments assigned by supervisors in addition to their course work/project. These findings are consistent with those of Olaitan et al (2009), Tichaona -Onias (2012, and Asogwa et al (2014).…”
Section: Resultssupporting
confidence: 93%
“…slowed me down in my project work/ writing', 'target respondents denied me access for data collection', 'my supervisor asked me to write and submit to him/her without any guide or materials', 'I am not computer literate enough to access the internet', 'sexual harassment from my supervisor', and 'my supervisor has poor knowledge of my topic to guide me properly'. These findings contradict those of Olaitan et al (2009), Tichaona -Onias (2012, and Asogwa et al (2014) as these researchers found that students encountered the aforementioned challenges.…”
Section: Challenges and Coping Strategies In Project Writingcontrasting
confidence: 75%
See 3 more Smart Citations